(untitled) (ModaPalavra e-periódico, 2008)
This article is a fragment of a larger article that discusses the importance of internal communication in companies. The proposal of this work was to show the importance of internal communication in organizations of small and medium businesses. The investigation was based on theoretical references and in the study of a practical case, which, together, have provided a solid basis for reflection on the subject. Whichever the size of an organization, small, medium or large, the relationship with the collaborators today assumes a strategic role. Internal communication is a competitive differential. In the case of small and medium businesses, archaic methods and administration amateurs make the challenge even greater, but not impossible. The managers of smaller size companies that are willing to change and adapt to the new reality will make an essential step in the growth and, especially, in the survival of the business itself. Based on studies and researches of various authors and conducting a survey of trends, the present study indicates that the locations of internal communication, allied with information technology is transforming the relations, among the agents of organizations and therefore, are very important when applied in the clothing industry, because of the great heterogeneity of their collaborators.